2012
DOI: 10.1152/ajpheart.00960.2011
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical and structural alterations in the aging rabbit heart and aorta

Abstract: Aging increases the risk for arrhythmias and sudden cardiac death (SCD). We aimed at elucidating aging-related electrical, functional, and structural changes in the heart and vasculature that account for this heightened arrhythmogenic risk. Young (5-9 mo) and old (3.5-6 yr) female New Zealand White (NZW) rabbits were subjected to in vivo hemodynamic, electrophysiological, and echocardiographic studies as well as ex vivo optical mapping, high-field magnetic resonance imaging (MRI), and histochemical experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 63 publications
(76 reference statements)
1
29
0
Order By: Relevance
“…Changes between the neonatal period and advanced age have been previously documented in rabbit (2 days vs. 5.6 yr) (1,6) and cat (6 wk vs. 18 yr) SAN function (1,6). Similarly, the present results demonstrate that IBR of the isolated mouse SAN and in cells isolated from the node are reduced in advanced age (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Changes between the neonatal period and advanced age have been previously documented in rabbit (2 days vs. 5.6 yr) (1,6) and cat (6 wk vs. 18 yr) SAN function (1,6). Similarly, the present results demonstrate that IBR of the isolated mouse SAN and in cells isolated from the node are reduced in advanced age (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, a parallel stiffening of the aorta and cardiac conduction system has been observed in an aging rabbit model. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-clinical studies in rabbits have shown an aging-related slowdown of electrical conduction velocity throughout the His-Purkinje network (8), which is manifested in humans by prolongation of the HV interval. Kuo et al (9) showed that the atrioventricular (AV) nodal recovery curve remains unchanged once one reaches adulthood, whereas the AV nodal effective refractory period becomes slightly longer after age 60 years (9).…”
Section: Pathophysiology Of Arrhythmias In the Elderlymentioning
confidence: 99%